Постать і творчість Євгена Сверстюка на сторінках газети «Луцьк молодий» (1999–2005 рр.) - Ольшевський, Ігор Едилович; Olshevsky, Igor (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті зроблено спробу відтворити хроніку публікацій та проаналізувати зміст статей, есеїв, публіцистичних виступів Є. О. Сверстюка, надрукованих у газеті Волинського державного університету імені Лесі Українки «Луцьк молодий» упродовж існування часопису (1999–2005 рр.), а також заміток та нарисів, присвячених письменникові-філософу. In this article author attempts to reproduce the chronicle of publications and analyze the content of articles, essays, journalistic performances E. A. Sverstiuk printed in the newspaper of Volyn State University of Lesya Ukrainka “Young Lutsk” for the duration of edition (1999–2005). Also in this article are analyzes notes and essays devoted to writer-philosopher. As a result of this analysis, the versatility of Sverstyuk’s personality and talent becomes evident. Also becomes evident his principled and uncompromising civil position during all his life, which could not to crack arrest and interrogation and the years in prison camps. Apelling to contemporary events the author proves the enduring actuality of publicist’s thoughts and opinions – especially in our difficult time.
Personality and Creativity of Eugene Sverstiuk in the Newspaper “Young Lutsk”
Keywords: Євген Сверстюк; Україна; шістдесятники; дисидентство; «Луцьк молодий»; Eugene Sverstyuk; Ukraine; Sixties; dissidence; “Young Lutsk”